A Linear Realization for the New Space–Time Superalgebras in 10 and 11 Dimensions; Modern Physics Letters A; Vol. 12, № 21 - Deriglazov A. A. (1997, 1997)
The new extensions of the Poincare superalgebra found recently in 10 and 11 dimensions are shown to admit a linear realization. The generators of the nonlinear and linear group transformations are shown to fall into equivalent representations of the superalgebra. The parametrization of the coset space G/H, with G a given extended supergroup and H the Lorentz subgroup, that corresponds to the linear transformations is presented.